Service security monitoring mechanism for application server cluster - Hongyao JU (Dianxin kexue)
For an application system，the workloads on the application servers’ key hardware and the working state of the application software are important factors affecting the system’s safety.Based on studies of the monitoring techniques for CPU，RAM，network traffic，software directories and software files of application servers，dynamic comprehensive monitoring，safety review and application software intelligent recovery were integrated，and an intelligent monitoring system was constructed for the application systems.The mechanisms and methodology of the monitoring system were illustrated.The system realized intelligent monitoring the working state of hardware and software，achieved the goal of automatic alarming，fault locating upon abnormal working states of the hardware or software and automatic recovery upon attacks to the software.